The Effectiveness of Direct Learning in Improving The Poetry Writing Ability of Grade VII Students of MTs Al-Falah Nipa - Lismiati Lismiati; Muhammad Yani; Arwan Arwan (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to examine the effectiveness of the direct instruction model in improving the poetry writing skills of seventh-grade students at MTs Al-Falah Nipa. The background of this research is the low quality of student-produced poems, particularly in terms of diction, structure, and imagination. This research employed a quantitative approach using a one-group pretest-posttest design. The instrument used was a poetry writing test assessed through five aspects: theme relevance, diction and figurative language, imagination, poem structure, and content coherence. The intervention was implemented over three sessions following the “I do, We do, You do” model. The results showed significant improvement in all aspects, especially structure and content coherence. The study concludes that direct instruction effectively, systematically, and purposefully enhances students’ poetry writing skills.